2010
DOI: 10.1016/j.otohns.2009.06.746
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of the application of a silk fibroin scaffold to otology

Abstract: The surgical treatment to repair chronic tympanic membrane perforations is myringoplasty. Although multiple autologous grafts, allografts, and synthetic graft materials have been used over the years, no single graft material is superior for repairing all perforation types. Recently, the remarkable properties of silk fibroin protein have been studied, with biomedical and tissue engineering applications in mind, across a number of medical and surgical disciplines. The present study examines the use of silk fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Silk fibroin supports adhesion, proliferation, and cell differentiation of cells in vitro, including human TM keratinocytes . A rat study reported hearing and healing benefits of silk fibroin membranes using only myringoplasty .…”
Section: Discussionmentioning
confidence: 99%
“…Silk fibroin supports adhesion, proliferation, and cell differentiation of cells in vitro, including human TM keratinocytes . A rat study reported hearing and healing benefits of silk fibroin membranes using only myringoplasty .…”
Section: Discussionmentioning
confidence: 99%
“…This research highlights the need for the evaluation and monitoring the phenotype of experimental cells at both low and high passage numbers to maintain experimental reliability and validity. A stable and committed keratinocyte cell population (in vitro) derived from the hTM is essential in our current goal of developing a biocompatible scaffold tailored specifically to enhancing keratinocyte growth with the long-term aim of utilization in myringoplasty (Ghassemifar et al 2010;Levin et al 2010 …”
Section: Discussionmentioning
confidence: 99%
“…By utilizing in vitro models that are biologically relevant to the tissue and parental cell type, important information can be revealed with a view towards reconstruction and replacement of diseased or damaged structures (Atala 2006), in this case chronic perforations of the hTM. We have reported the culture of hTM epithelial cells (hTMk) on silk substrates (Levin et al 2010) with the aim of testing alternative grafts for repairing perforated human eardrums. However, if cultured primary cells are to be used as the progenitors of an engineered tissue or organ, their phenotypic and genotypic integrity must be maintained throughout the culture process.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] For more than four decades, low-level laser therapy has been regarded in many medical fields as an efficient approach to wound healing, inflammation reduction and disease treatment. However, in light of the costs involved, long hospitalisation period and consequences of surgery, more recent studies have focused on alternative treatment approaches such as myringoplasty, graft myringoplasty and, most recently, laser therapy.…”
Section: Introductionmentioning
confidence: 99%